A more in-depth interpretation of MMPI-2 in MS patients by using Harris and Lingoes subscales. Issue 5 (3rd September 2017) - Incerti, Chiara C.; Argento, Ornella; Pisani, Valerio; Magistrale, Giuseppe; Sabatello, Ugo; Caltagirone, Carlo; Nocentini, Ugo
ABSTRACT: Multiple Sclerosis (MS) is frequently associated with neuropsychiatric abnormalities. The aim of our study was to discriminate between psychosomatic disturbances and MS physically-related symptoms using the Harris-Lingoes subscales of the Minnesota Multiphasic Personality Inventory-2 (MMPI-2). Forty-six MS out-patients (35 females; mean age = 44.5); and 82 healthy volunteers (62 females; mean age = 46.5) were evaluated with MMPI-2 questionnaire. The frequency distribution of MMPI-2 clinical scales with high scores (> = 65) and the related Harris-Lingoes subscales were analyzed for both MS patients and healthy control subjects. Data analysis showed elevated scores in 47.8% of the patients mainly on MMPI-2 clinical scales 1, 2, and 3. The Harris-Lingoes subscales analysis allowed us to isolate and identify physical symptoms contributing to elevation of MMPI-2 clinical scales, reduce the occurrence of false positives (MMPI-2 clinical scales elevations mainly due to MS physical disability) and provide a more detailed description of psycho-emotional symptoms of MS patients. In conclusion, our study shows the utility of Harris-Lingoes subscales analysis when MMPI-2 is used for psychological assessment of MS patients.